Time-varying investment dynamics in the USA - Ivan Mendieta-Mu\~noz (The University of Utah, Department of Economics, 2024)
We study the time-varying effects of Tobin's q and cash flow on investment dynamics in the USA using a vector autoregression model with drifting parameters and stochastic volatilities estimated via Bayesian methods. We find significant variation over time of the response of investment to shocks in both variables. The time-varying sensitivity of investment to a shock in Tobin's q (cash flow) decreased (increased) since the early 1960s through the early 1980s, increased (decreased) since the early 1980s through the early 2000s, and it has decreased (increased) importantly again since then. Our results show that, although Tobin's q and cash flow are complementary sources of information for investment decisions, their relative importance for investment dynamics has varied considerably over time, so both variables also represent alternative sources of information for short-run fluctuations in investment.
Keywords: C11; C32; E22; E32; G31; 330; Investment dynamics; Tobin's q; cash flow; time-varying parameters; vector autoregression; stochastic volatility